DESENVOLVIMENTO, CARACTERIZAÇÃO, ESTUDOS DE ESTABILIDADE, GENOTOXICIDADE, CITOTOXICIDADE E ECOTOXICIDADE DE SISTEMAS NANOESTRUTURADOS CONTENDO ÓLEO ESSENCIAL DE GENGIBRE OU TRANS-ANETOL - Pinto, Cláudia Grigolo (2018)
This study explored the profile of the ginger essential oil and of the trans-anethole, which are medicinal plants active ingredients extensively used in traditional medicine. These have been popularized in recent years, due to several properties, which are, however, significantly toxic. These ingredients were manipulated by methods used in nanotechnology. Thus, lipid- and polymer-based nanostructure systems, such as nanocapsules, nanoemulsions, and lipid carriers were produced. For the polymer systems, a preliminary study was carried out in order to determine which polymer would be used, which was later tested using a polymer swelling test. After the definition of the polymer and of the best methodology, the systems were produced. These had their physical-chemical parameters, such as polydispersity index, zeta potential, mean particle diameter, pH and stability evaluated for 90 days to verify in which conditions they were stable, thus allowing the determination of the best storage conditions. Nanocapsules, nanoemulsions, and lipid carriers containing ginger essential oil were produced. Similarly, systems which contained trans-anethole were produced. For comparison purposes, blank systems, which do not have the studied ingredients, were also produced. After characterization and stability studies, each of the systems was analyzed for the following: cytotoxicity and cell viability in macrophages by the MTT assay, genotoxicity by the Comet assay, antimicrobial activity by disk diffusion, antimicrobial activity by broth microdilution, and ecotoxicity by bioassay with Artemia. As for the antimicrobial activity, only some of the formulations presented significant activity on the analyzed strains. In general, the results obtained indicated a reduction in the cyto-, geno- and the eco-toxicity of the nanostructured systems when compared with the free forms of the studied ingredients and their respective controls. This study made it possible to corroborate other studies which have also demonstrated the great potential of the use of nanotechnology to explore the profile of medicinal plants. Through these methodologies, their toxicity could be reduced and pharmacological and environmental safety could be promoted. Considering the results obtained, four scientific articles were produced and submitted to scientific journals.